Identifikasi Gaya Belajar Mahasiswa Pendidikan Biologi di Masa New Normal - Gusmaweti Gusmaweti; Wince Hendri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to identify the learning styles of Bung Hatta University Biology Education students and learning solutions in the New Normal era. Types of learning styles studied include visual, auditory and kinesthetic learning styles. The samples were determined by total sampling with 37 students of Biology Education at Bung Hatta University in Padang who were active in the odd semester 2020/2021. The research instrument was a valid questionnaire for the types of learning styles. Overall, the results showed that overall Biology Education students had a dominant kinesthetic learning style of 35%, a visual learning style of 33%, and an auditory learning style of 32%. In conclusion, Biology Education students tend to learn Kinesthetic learning styles. This study provides information to lecturers who teach in the study program and students of the Biology Education study program to use appropriate and varied learning methods and media during the lecture process. Keywords: Auditorial, Learning Style, Kinesthetic, New Normal, Visual